Post‐diagnosis adiposity and colorectal cancer prognosis: A Global Cancer Update Programme ( CUP Global) systematic literature review and meta‐analysis - Becerra‐Tomás, N; Markozannes, G; Cariolou, M; Balducci, K; Vieira, R; Kiss, S; Aune, D; Greenwood, DC; Dossus, L; Copson, E; Renehan, AG; Bours, M; et al. (Wiley, 2024)
The adiposity influence on colorectal cancer prognosis remains poorly characterised. We performed a systematic review and meta‐analysis on post‐diagnosis adiposity measures (body mass index [BMI], waist circumference, waist‐to‐hip ratio, weight) or their changes and colorectal cancer outcomes. PubMed and Embase were searched through 28 February 2022. Random‐effects meta‐analyses were conducted when at least three studies had sufficient information. The quality of evidence was interpreted and graded by the Global Cancer Update Programme (CUP Global) independent Expert Committee on Cancer Survivorship and Expert Panel. We reviewed 124 observational studies (85 publications). Meta‐analyses were possible for BMI and all‐cause mortality, colorectal cancer‐specific mortality, and cancer recurrence/disease‐free survival. Non‐linear meta‐analysis indicated a reverse J‐shaped association between BMI and colorectal cancer outcomes (nadir at BMI 28 kg/m2). The highest risk, relative to the nadir, was observed at both ends of the BMI distribution (18 and 38 kg/m2), namely 60% and 23% higher risk for all‐cause mortality; 95% and 26% for colorectal cancer‐specific mortality; and 37% and 24% for cancer recurrence/disease‐free survival, respectively. The higher risk with low BMI was attenuated in secondary analyses of RCTs (compared to cohort studies), among studies with longer follow‐up, and in women suggesting potential methodological limitations and/or altered physiological state. Descriptively synthesised studies on other adiposity‐outcome associations of interest were limited in number and methodological quality. All the associations were graded as limited (likelihood of causality: no conclusion) due to potential methodological limitations (reverse causation, confounding, selection bias). Additional well‐designed observational studies and interventional trials are needed to provide further clarification.